Introducing Marketing - Burnett, John; Open Textbook Library (Open Textbook Library, 2011)
Through good economic times and bad, marketing remains the pivotal function in any business. Determining and satisfying the needs of customers through products that have value and accessibility and whose features are clearly communicated is the general purpose of any business. It is also a fundamental definition of marketing. This text introduces students to the marketing strategies and tools that practitioners use to market their products.
1. Introducing marketing -- 2. Understanding and approaching the market -- 3. Marketing research: an aid to decision making -- 4. Understanding buyer behavior -- 5. External considerations in marketing -- 6. Marketing in global markets -- 7. Introducing and managing the product -- 8. Communicating to mass markets -- 9. Pricing the product -- 10. Channel concepts: distributing the product
In English.
Description based on online resource
Keywords: Business -- Textbooks; Marketing -- Textbooks